2011
DOI: 10.1093/ejechocard/jer138
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular systolic function assessment: rank of echocardiographic methods vs. cardiac magnetic resonance imaging

Abstract: A systolic long-axis peak velocity of <11 cm/s at the lateral tricuspid annulus most accurately detects moderately impaired RVEF as obtained by MRI; severely reduced RVEF ≤30% is best detected by RV MPI at a value of >0.50.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
133
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(149 citation statements)
references
References 24 publications
13
133
2
1
Order By: Relevance
“…Our own experience and that of other authors has found fractional area change to suffer from large interobserver variations [33], often the result of difficulty in clearly defining endocardial borders due to RV trabeculations. Furthermore, accurate measurement of RV area is limited by the complex geometry of this chamber.…”
Section: Limitationsmentioning
confidence: 69%
“…Our own experience and that of other authors has found fractional area change to suffer from large interobserver variations [33], often the result of difficulty in clearly defining endocardial borders due to RV trabeculations. Furthermore, accurate measurement of RV area is limited by the complex geometry of this chamber.…”
Section: Limitationsmentioning
confidence: 69%
“…Significant improvement of RVFAC after LVAD implantation may attenuate the association between RVFAC and residual TR. Furthermore, RVFAC emerged as a poor parameter for the determination of RV contractility in recent studies,29, 30 suggesting that, in the presence of TR, estimates of radial contraction may misdiagnose the presence of RV dysfunction because of the decrease in RV afterload caused by the leaking valve, just as the LVEF assessment is limited by MR 13. Tricuspid annular plane systolic excursion, RV index of myocardial performance and/or assessment using 3‐dimensional echocardiography may provide additional information of RV contractility and its association with residual TR 30, 31.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6). RVFAC expresses the percentage change of the calculated right ventricular areas between the enddiastole right ventricular area (the end of the part of the cardiac cycle when the heart relaxes, when the heart is at its biggest) and end-systole right ventricular area (the end of the cardiac contraction, when the heart is at its smallest) (Pavlicek et al 2011; P. C. Frommelt et al 2012).…”
Section: Interstage Mortalitymentioning
confidence: 99%
“…The gold standard method to measure right ventricular ejection fraction is cardiac magnetic resonance imaging (MRI) and normal values of RVEF measured by MRI are 49 % to 72 % (Pavlicek et al 2011;Larose et al 2007). Unfortunately, MRI was only performed on a subgroup of patients for the SVR trial.…”
Section: Right Ventricular Function Measurementsmentioning
confidence: 99%